XILANASES EM DIETAS COM REDUÇÃO ENERGÉTICA PARA POEDEIRAS COMERCIAIS - MENDONÇA, Ana Paula Vargas; ANDRADE, Gislaine da Cunha; SANTANA, Patrícia Gomes; BAIRROS, Eliane Corrêa; ROCHA, Bruna de Jesus; GARCIA, Elis Regina de Moraes (ANAIS DO ENIC, 2022)
-